Jawabanmu

2014-08-24T16:23:44+07:00
H(x) = ax + b                                        
h(5)=a.5 + b = 5a + b  =16
h(4)=a.4+ b =  4a + b  =11
                      ________ _
                         a =  5

4a + b = 11                =>  20 + b =11            =>      h(-1) = a .(-1) = 5 x -1=-5
4x5 + b =11                     b = 11 - 20 = -8                b = -8   => h(-1) = -5  + -8 
                                                                                                                = -13 
2014-08-24T16:36:42+07:00
H(x) = ax + b                                        
h(5)=a.5 + b = 5a + b  =16
h(4)=a.4+ b =  4a + b  =11
                      ________ _
                         a =  5

4a + b = 11 =  20 + b =11 =  h(-1) = a .(-1) = 5 x -1=-5
4x5 + b =11       b = 11 - 20 = -8                b = -8   => h(-1) = -5  + -8 
                                                                                                                = -13